Predicted health care profile after transition to adult care in Turner syndrome children—experience of single center - Witkowska-Krawczak, Ewa; Erazmus, Michał; Majcher, Anna; Pyrżak, Beata; Kucharska, Anna Małgorzata (Frontiers in Pediatrics, 2023)
INTRODUCTION: Turner Syndrome (TS) is caused by the complete or partial loss of one of the X chromosomes in all or some female cell lines. The variable genotypes are responsible for a large phenotypic diversity, nevertheless most studies emphasize a weak correlation between genotype and phenotype. The study aimed to assess the occurrence of defects and diseases depending on the karyotype in patients with TS and correlation with the predicted health care profile after the transition to adulthood. MATERIALS AND METHODS: 45 patients of the Department of Endocrinology and Pediatrics of the Medical University of Warsaw in 1990-2002 were analyzed. Girls were divided into 2 subgroups: “A”, which included 16 patients with the karyotype 45,X, and “B”, which included 29 girls with mosaic karyotypes. Based on the literature data, characteristic phenotypic features and the typical defects or diseases accompanying TS were selected, and the frequency of their occurrence was compared in both subgroups. Accordingly to this data, the predicted medical care profile was determined. RESULTS: In our study, patients with complete monosomy of the X chromosome had more characteristic phenotypic features. They needed sex hormone replacement therapy more often and started to menstruate spontaneously much less frequently (only 18.18% in monosomy vs 73.91% in mosaic patients, p=0.006). In patients with monosomy, congenital defects of the circulatory system were found more often (46.67% vs 30.77%). The diagnosis in patients with mosaic karyotype was more often delayed, therefore the optimal time of growth hormone therapy was shorter. In our study, the X isochromosome determined the higher prevalence of autoimmune thyroiditis (83.33% vs 12.5%, p=0.049). We didn’t find a correlation between the type of karyotype and health care profile after the transition, most of the patients needed more than 2 specialists. Most often, they required: gynecologists, cardiologists, and orthopedics. CONCLUSIONS: After the transition from pediatric to adulthood, patients with TS need multidisciplinary care, but not all need the same kind of assistance. The phenotype and comorbidities determine the profile of patients' health care, however it wasn’t directly related to the type of karyotype in our study.